EVALUASI KEGIATAN PENDAMPINGAN LITERASI DIGITAL “HOAKS” PADA KELOMPOK PENGAJIAN PEREMPUAN - Rohmatin Alfianistiawati; Pramana Herjati Putra Dionchi; Hasna Bararah; Megasari Noer Fatanti (Universitas Negeri Malang, 2022)
The increasing circulation of false/hoax information amid the increasing number of internet users in Indonesia is why understanding media literacy, especially digital information, needs to be given to all levels of society, including housewives (IRT), who are often actors who spread hoaxes and affected victims. This article discusses efforts to increase the understanding of the study group about